A formação de agenda de políticas públicas de turismo em âmbito local: os casos de Ouro Preto (MG) e Paraty (RJ) - Silva, Fernanda Cristina da (2015)
This thesis aims to understand the agenda setting process for tourism public policy at the local level, as well as to identify the different agents influencing this process. The thesis is theoretically based on the literature of public policies analysis, especially regarding to the agenda setting process. Aiming to understand the context under investigation, the literature on tourism and tourism public policies is also addressed in the present study. In order to know an exemplar case (recognizably important) about how the public tourism management is addressed at the local level, the Tourism Model of Barcelona (Spain) was analysed. This analysis provided the statement of some propositions, which served as reference for analysing two Brazilian cities: Ouro Preto (MG) and Paraty (RJ). The data collection was carried out in locus and involved both document analysis and semi-structured interviews with key public and private stakeholders involved in the tourism activity in each municipality. Besides that, secondary data were used in order to supplement the primary data. The data interpretation strategy involved within-case (in-depth analysis of each case) and cross-case (analysis between cases) and the data analysis was developed through the method of content analysis. The research results indicated the following factors as elements influencing how tourism is considered by local governments: the level of dependence on tourism activity; the tourism development stage; the network of actors involved within the policy; the priority given to the topic by the local government; and the political context. In general, three perspectives were identified to explain how the tourism theme rise on the local governments agenda: tourism as an opportunity; tourism as a solution to diverse problems related to other areas; and tourism as a problem (social and sectorial). In both Brazilian cases, the results showed that the network of actors involved in local tourism policy is poorly articulated and the interaction between them (which occurs mainly through the Municipal Tourism Council - Ouro Preto case, or from its formation or of other arrangements – Paraty case) still cannot influence public policy. However, it was evidenced in Paraty that the isolated action of an actor (in this case, the private sector), has managed to get some themes rise as public policies issues. Although there is no clear cause - effect relation, the evidences suggest that the government actions on only a few aspects of tourism, favouring special interests, and inaction in others, affecting mainly the citizens’ interests, can boost an unequal tourism development model, in which the benefits are concentrated and the costs are dispersed.